Do Low-Income Students Have Equal Access to Effective Teachers?. (June 2022) - Isenberg, Eric; Max, Jeffrey; Gleason, Philip; Deutsch, Jonah
We examine access to effective teachers for low-income students in 26 geographically dispersed school districts over a 5-year period. We measure teacher effectiveness using a value-added model that accounts for measurement error in prior test scores and peer effects. Differences between the average value added of teachers of high- and low-income students are 0.005 standard deviations in English/language arts and 0.004 standard deviations in math. Differences between teachers of Black, Hispanic, and White students are also small. Rearranging teachers to obtain perfect equity would do little to narrow the sizable student achievement gap between low- and high-income students. We also show that a higher proportion of novice teachers in high-poverty schools contributes negligibly to differences in access to effective teachers.